Preliminary Evidence Supporting a Framework of Psychological Adjustment to Inflammatory Bowel Disease - Kiebles, Jennifer L. (2010)
BACKGROUND: Adjustment to chronic disease is a multidimensional construct described as successful adaptation to disease-specific demands, preservation of psychological well-being, functional status, and quality of life. Inflammatory bowel disease (IBD) can be particularly challenging due to the unpredictable, relapsing and remitting course of the disease. METHODS: All participants were patients being treated in an outpatient gastroenterology clinic at a university medical center. Participants completed a survey of questionnaires assessing illness perceptions, stress, emotional functioning, disease acceptance, coping, disease impact, and disease-specific and health-related quality of life. Adjustment was measured as a composite of perceived disability, psychological functioning, and disease-specific and health-related quality of life. RESULTS: Participants were 38 adults with a diagnosis of either Crohn’s disease (45%) or ulcerative colitis (55%). We observed that our defined adjustment variables were strongly correlated with disease characteristics (r = 0.33–0.80, all P < 0.05), an emotional representation of illness (r = 0.44–0.58, P < 0.01), disease acceptance (r = 0.34–0.74, P < 0.05), coping (r = 0.33–0.60, P < 0.05), and frequency of gastroenterologist visits (r = 0.39–0.70, P < 0.05). Better adjustment was associated with greater bowel and systemic health, increased activities engagement and symptom tolerance, less pain, less perceived stress, and fewer gastroenterologist visits. All adjustment variables were highly correlated (r = 0.40–0.84, P < 0.05) and demonstrated a cohesive composite. CONCLUSIONS: The framework presented and results of this study underscore the importance of considering complementary pathways of disease management including cognitive, emotional, and behavioral factors beyond the traditional medical and psychological (depression and anxiety) components.